2018
DOI: 10.1016/j.watres.2017.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Pore diffusion limits removal of monochloramine in treatment of swimming pool water using granular activated carbon

Abstract: Overall apparent reaction rates for the removal of monochloramine (MCA) in granular activated carbon (GAC) beds were determined using a fixed-bed reactor system and under conditions typical for swimming pool water treatment. Reaction rates dropped and quasi-stationary conditions were reached quickly. Diffusional mass transport in the pores was shown to be limiting the overall reaction rate. This was reflected consistently in the Thiele modulus, in the effect of temperature, pore size distribution and of grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Many previous studies showed that the reduction of monochloramine in a fixed GAC bed can be described in sufficient detail using first order reaction kinetics (Skibinski et al, 2018;Kim, 1977;Scaramelli and Digiano, 1977;Kim and Snoeyink, 1980).…”
Section: Experimental Determination Of the Carbon Reactivity Nh 4 + Yield And N 2 Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies showed that the reduction of monochloramine in a fixed GAC bed can be described in sufficient detail using first order reaction kinetics (Skibinski et al, 2018;Kim, 1977;Scaramelli and Digiano, 1977;Kim and Snoeyink, 1980).…”
Section: Experimental Determination Of the Carbon Reactivity Nh 4 + Yield And N 2 Yieldmentioning
confidence: 99%
“…The procedure for determining k app in fixed-bed column experiments under fully controlled conditions has been described previously by the authors (Skibinski et al, 2018). In brief, a laboratory-scale fixed-bed column with known bed volume (V bed )…”
Section: Experimental Determination Of the Carbon Reactivity Nh 4 + Yield And N 2 Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that to carry out a proper rinsing process, the DIN standard recommends the use of 4 -6 m 3 for each m 2 of filter bed. In the case of larger facilities, this generates large volumes of washings, which have the potential for re-use [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The dechlorination rate is critical to evaluate the performance of the activated carbon, particularly for activated carbon filter manufacturers. Although the kinetic reaction by activated carbon for chlorimines removal was intensively studied (Sakuma et al 2015;Matsushita et al 2017;Skibinski et al 2018), the direct kinetic performance of free chlorine removal by activated carbon was not well understood. Since the free chlorine acts as a precursor to form the chlorinated DBPs, it is of great importance to study the free chlorine removal by activated carbon.…”
Section: Introductionmentioning
confidence: 99%